Studi Kepadatan Zooxanthella Pada Tridacna squamosa dan Hippopus hippopus di Perairan Desa Toli-Toli dan Desa Sawapudo Sulawesi Tenggara - Ira, Ira; Sarita, Abdul Haris; Afu, Alirman (AQUASAINS, 2014)
Zooxanthellae is one food source of clams. Zooxanthellae stay on the mantle tissue and photosynthesis activity. Quantity of photosynthesis is influenced by the zooxanthellae density and type of clam.  This study aims to determine the density zooxanthellae of symbiotic with clams Tridacna squamosa and Hippopus hippopus. The usefulness of the research will provide data and information on the density zooxanthellae of the Tridacna squamosa zooxanthella and Hippopus hippopus clams and as consideration for site selection translocated clams. The study was conducted in August-December 2013 by doing sampling clams in Toli-Toli and Sawapudo village waters. Mantle tissue clams taken 1 cm2 and analyzed in the laboratory. The results showed that Tridacna squamosa has the highest density zooxanthellae compared with Hippopus hippopus. Tridacna squamosa and Hippopus hippopus shell size > 15 cm has the highest density zooxanthellae compared with shell size <15 cm. High suspended solids in the water affect the density zooxanthellae of clams.